The Analysis Model Of The Causal Influence Factors Of Attractiveness And Commitment To Export Affecting Export Capability - et. al., Banterng Sriard, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Abstract: The objectives of this research aim 1) to investigate factors which are related to the attractiveness and commitment of food exporting industry and 2) to develop a model of causal influence of attractiveness and commitment on food exporting industry. The researcher collected samples from a specific target group of 145 companies. Data were analyzed by using descriptive statistics. Moreover, the researcher also analyzed information by descriptive statistics. In the part of analytical statistics analyzed, researcher using factors analysis and the causal influence analysis between variables according to the conceptual framework by LISREL program. The results revealed that attractiveness of export had influence on export capability. On the contrary, the analysis showed that export commitment had positive influence on the capability of exporting. Assessment on goodness of fit from the model found that export capability was consistent with the empirical data, the chi-square =185.57, the degrees of freedom = 99, chi -square relative (x2/df) =1.87, the probability (P-value) = 0.00, goodness of fit index (GFI) = 0.98, comparative fit index (CFI) = 0.98, Root mean square error of approximation (RMSEA) = 0.50..